HIF‐1α modulates pancreatic cancer ECM proteins via the TGF‐β1/Smad signaling pathway introduction - Guo, Houle; Zhao, Zhanxue; Liu, Linxun (Frontiers in Oncology, 2025)
IntroductionPancreatic cancer is characterized by its aggressive nature and poor prognosis, ranking among the most lethal malignancies. The tumor microenvironment, particularly the extracellular matrix (ECM), plays a crucial role in cancer progression. This study investigated the relationship between hypoxia-inducible factor-1α (HIF-1α) and transforming growth factor-β1 (TGF-β1) in regulating ECM protein expression in pancreatic cancer.MethodsPANC-1 cells were cultured under both normoxic and hypoxic conditions. Pharmacological inhibition of HIF-1α and TGF-β1, as well as TGF-β1 stimulation, were employed to evaluate ECM protein expression. HIF-1α knockdown experiments and co-immunoprecipitation were performed to assess molecular interactions. Clinical specimens were analyzed for HIF-1α and TGF-β1 expression.ResultsHIF-1α was found to modulate ECM protein expression through the TGF-β1/Smad signaling pathway. Pharmacological inhibition of either HIF-1α or TGF-β1 significantly decreased the expression of ECM proteins, while TGF-β1 stimulation enhanced their production. HIF-1α knockdown abolished TGF-β1-induced ECM protein expression, indicating that HIF-1α is essential for TGF-β1-mediated ECM regulation. Co-immunoprecipitation experiments revealed a physical interaction between HIF-1α and TGF-β1. Clinical specimens showed significantly elevated expression of both HIF-1α and TGF-β1 in pancreatic cancer tissues compared to adjacent normal tissues, correlating with advanced disease stages.DiscussionThese findings elucidate a novel mechanism where HIF-1α and TGF-β1 cooperatively regulate ECM production in pancreatic cancer, providing potential therapeutic targets for intervention.